Microfluidic generation of encapsulated droplet interface bilayer networks (multisomes) and their use as cell-like reactors. - Elani,Y; Solvas,XC; Edel,JB; Law,RV; Ces,O (Chemical Communications, 2016)
Compartmentalised structures based on droplet interface bilayers (DIBs), including multisomes and compartmentalised vesicles, are seen by many as the next generation of biomimetic soft matter devices. Herein, we outline a microfluidic approach for the construction of miniaturised multisomes of pL volumes in high-throughput and demonstrate their potential as vehicles for in situ chemical synthesis.